View of the Jalavatayanas (perforated windows) above the Vedika (railing) - Temples of India Project Team (Jio Institute, 2024)
Closer view of the jalavatayanas (perforated windows) above the vedika (railing) of the kakshasana (seat backs) of the mandapa (pillared hall) of the Mahanaleshwar Temple. The corner pillars of this mandapa support protruding chajja (balcony). The walls corresponding to the pillars have devakoshthas (niches) with divine figures and dikapalas (gods of cardinal directions) in them. The pillar capitals have bharavahakas (dwarf-like icons that are shown bearing the weight of the temple).